TerriStories®, a serious game to improve long-term autonomous management of natural resources and land - d'Aquino, Patrick (Perspective, 2023)
Version française de l'article Versão portuguesa do artigo Versión en español del artículo Although participatory and inclusive approaches have been recognised as necessary for involving local people in the management of resources and territories, their impact often remains limited in the long term, whether at the local level or for broader territories. Based on this observation, a CIRAD team developed a method in the late 1990s using a serious game, TerriStories®. The effects of the first trial in Senegal in 1998-1999 are still seen today at the local and national levels. Applied to the management of local territories, then to the definition of national land and environmental regulations, the method has succeeded – in all of the countries in which it has been deployed – in driving collective endogenous proposals that the actors themselves then deliver and implement according to their own requirements.